GAMBARAN GAYA KEPEMIMPINAN, MOTIVASI KERJA SERTA KINERJA KARYAWAN CIPANAS INDAH HOTEL DI GARUT - Sari, Anita Permata; Mulyadi, Hari; Tarmedi, Eded (Journal of Business Management Education (JBME), 2018)
Purpose - This study aimed to gain a sense o1qf leadership style, gain a working motivation overview, andÂ  overview of employee performanceDesign / methodology / approach - The method used is an Explanatory Survey with a sample size of 44 respondents. The data analysis technique used is multiple linear regression with spss 20.0 for windows programming tool.Findings- Research results show that leadership style is in the category of effective, work motivation is in the strong category and employee performance is in good category. Leadership style and work motivation have a positive influence on employee performanceOriginality / value - This study provides a basis for understanding the style of leadership and work motivation that affects employee performance. The difference of this research with previous research is located on the object of research that is Hotel Cipanas Indah company and use theory or reference different from previous researcher